2013
DOI: 10.1124/mol.113.090043
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 Inhibitors Enhance Chemotherapy Killing in Gastrointestinal/Genitourinary Cancer Cells

Abstract: The present studies determined whether clinically relevant phosphodiesterase 5 (PDE5) inhibitors interacted with clinically relevant chemotherapies to kill gastrointestinal/genitourinary cancer cells. In bladder cancer cells, regardless of H-RAS mutational status, at clinically achievable doses, PDE5 inhibitors interacted in a greater than additive fashion with doxorubicin/mitomycin C/gemcitabine/ cisplatin/paclitaxel to cause cell death. In pancreatic tumor cells expressing mutant active K-RAS, PDE5 inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 56 publications
2
59
0
1
Order By: Relevance
“…New therapeutic approaches that could translate to the clinic for this malignancy are urgently required. In two recently published studies we demonstrated that phosphodiesterase 5 (PDE5) inhibitors enhanced the toxicity of standard of care chemotherapies in bladder and pediatric CNS tumors (22, 23). In the present studies, we determined whether PDE5 inhibitors interacted with OSU-03012 to kill glioma cells and we defined the molecular mechanisms by which ER stress effector pathways regulated OSU-03012 toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…New therapeutic approaches that could translate to the clinic for this malignancy are urgently required. In two recently published studies we demonstrated that phosphodiesterase 5 (PDE5) inhibitors enhanced the toxicity of standard of care chemotherapies in bladder and pediatric CNS tumors (22, 23). In the present studies, we determined whether PDE5 inhibitors interacted with OSU-03012 to kill glioma cells and we defined the molecular mechanisms by which ER stress effector pathways regulated OSU-03012 toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…These data further support our findings that BRD4 is a critical regulator in bladder cancer progression (35). It has been demonstrated that a number of therapeutic strategies enhanced chemotherapy in human bladder cancer cells (36,37). Whether treatment with JQ1 combined with other chemotherapeutics simultaneously exert the synergistic effect in bladder cancer therapy needs to be answered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody reagents, other kinase inhibitors, caspase inhibitors cell culture reagents, and non-commercial recombinant adenoviruses have been previously described. [39][40][41][42] Previously characterized semi-established GBM5 / GBM6 / GBM12 / GBM14 glioblastoma cells were supplied by Dr. C.D. James (University of California, San Francisco) and Dr. J.N.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were isolated at the indicated times and SDS PAGE and immunoblotting was performed as described in refs. [39][40][41][42] Blots were observed by using an Odyssey IR imaging system (LI-COR Biosciences, Lincoln, NE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation